Deletions of exons with regulatory activity at the DYNC1I1 locus are associated with split-hand/split-foot malformation: array CGH screening of 134 unrelated families - Naeimeh Tayebi; Aleksander Jamsheer; Ricarda Flöttmann; Anna Sowińska‐Seidler; Sandra C. Doelken; Barbara Oehl‐Jaschkowitz; Wiebke Hülsemann; R. Habenicht; Eva Klopocki; Stefan Mundlos; Malte Spielmann (2014)
A growing number of non-coding regulatory mutations are being identified in congenital disease. Very recently also some exons of protein coding genes have been identified to act as tissue specific enhancer elements and were therefore termed exonic enhancers or "eExons". We screened a cohort of 134 unrelated families with split-hand/split-foot malformation (SHFM) with high resolution array CGH for CNVs with regulatory potential. In three families with an autosomal dominant non-syndromic SHFM phenotype we detected microdeletions encompassing the exonic enhancer (eExons) 15 and 17 of DYNC1I1. In a fourth family, who had hearing loss in addition to SHFM, we found a larger deletion of 510 kb including the eExons of DYNC1I1 and, in addition, the human brain enhancer hs1642. Exons 15 and 17 of DYNC1I1 are known to act as tissue specific limb enhancers of DLX5/6, two genes that have been shown to be associated with SHFM in mice. In our cohort of 134 unrelated families with SHFM, deletions of the eExons of DYNC1I1 account for approximately 3% of the cases, while 17p13.3 duplications were identified in 13% of the families, 10q24 duplications in 12%, and TP63 mutations were detected in 4%. We reduce the minimal critical region for SHFM1 to 78 kb. Hearing loss, however, appears to be associated with deletions of a more telomeric region encompassing the brain enhancer element hs1642. Thus, SHFM1 as well as hearing loss at the same locus are caused by deletion of regulatory elements. Deletions of the exons with regulatory potential of DYNC1I1 are an example of the emerging role of exonic enhancer elements and their implications in congenital malformation syndromes.